Peer Counseling Program for Preventing The Unintended Pregnancy Among Adolescents - Hidayat, Elsy Junilia; Hidayah, Nurul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
This study aims to review the effectiveness of primary prevention strategies aimed at delaying sexual intercourse, improving the use of birth control, and reducing the incidence of unintended pregnancy in adolescents. This study examined the effectiveness of peer counseling to reduce unintended pregnancy in adolescents because, in adolescence, a person will spend more time and do modeling with peers. This research used a quasi-experimental research design with a nonrandomized control group design with two groups: experimental and control, aiming to design a program intervention for groups of adolescents at risk to reduce unintended pregnancy, using a one-shot case study pattern. The researchers gave treatment in a group of at-risk adolescent subjects aged 12-15 years. The findings of this research show that intervention with peer counseling technique is a primary preventive to adolescents. Peer counseling can be increasing the reproduction health knowledge of adolescents. Peer counseling also increasing the parent and teachers knowledge of adolesce e’s growth. The level of cognitive change may improve adolescents' behavior and decrease the number of unintended pregnancies. Applications of this study: Recommendations for the most efficacious programs may vary by target age group, race,  culture, and community. Despite limitations, core principles can be applied to all teen pregnancy prevention programs and supply administrators with the information to champion particular practices to achieve optimal results in preventing teen pregnancy.